Iridotomy with red krypton laser. Issue 4 (April 1986) - Yassur, Y; David, R; Rosenblatt, I; Marmour, U
Abstract : Iridotomy with red krypton laser instead of blue-green argon laser was performed on 68 eyes with various types of angle-closure glaucoma. Patent iridotomy was obtained in all the eyes, mostly in one working session. In eight eyes secondary closure by pigment needed reopening with a few applications at the iridotomy site. There were no immediate or late complications of importance, the main advantage of the technique being the avoidance of the corneal epithelial and endothelial burns which commonly occur during argon laser iridotomy, particularly when the anterior chamber is shallow.